2011
DOI: 10.1063/1.3651193
|View full text |Cite
|
Sign up to set email alerts
|

Precise simulation of the freezing transition of supercritical Lennard-Jones

Abstract: The fluid-solid transition of the Lennard-Jones model is analyzed along a supercritical isotherm. The analysis is implemented via a simulation method which is based on a modification of the constrained cell model of Hoover and Ree. In the context of hard-sphere freezing, Hoover and Ree simulated the solid phase using a constrained cell model in which each particle is confined within its own Wigner-Seitz cell. Hoover and Ree also proposed a modified cell model by considering the effect of an external field of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
46
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(49 citation statements)
references
References 43 publications
3
46
0
Order By: Relevance
“…The details of these simulations have been discussed in previous work. [5][6][7][8][9] As is evident in Fig. 1, at very low densities and pressures, the system behaves as an ideal gas, i.e., p* ∼ = ρ.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The details of these simulations have been discussed in previous work. [5][6][7][8][9] As is evident in Fig. 1, at very low densities and pressures, the system behaves as an ideal gas, i.e., p* ∼ = ρ.…”
mentioning
confidence: 86%
“…Similar mechanical stability points have also been seen in constant-volume simulations of soft-sphere and Lennard-Jones systems. 3,4 Recently, Nayhouse et al [5][6][7][8][9] proposed a simulation method for liquid-solid transitions which is based on constant-pressure simulations of generalized cell models. They found that the mechanical stability point of the solid phase, as modeled through the constrained cell model, appears in the form of an inflection point at about the same density and pressure as in previous work.…”
mentioning
confidence: 99%
“…[1][2][3] This task is, however, computationally demanding due to the substantial density range (from the low-ρ ideal-gas to the high-ρ incompressible regime) that must be sampled in a single simulation. Regarding system-size effects, previous work [3][4][5] associated with finite-size scaling analysis of liquid-solid coexistence at fixed T * using cell models indicates that the estimate of the pressure for N = 256 differs by 4%-6% from the N = ∞ value. These differences are expected to be somewhat larger for the triple-point parameters due to the highly compressible nature of the gas phase.…”
mentioning
confidence: 99%
“…The likely explanation for this discrepancy is the highly compressible nature of the gas phase. Recently, Nayhouse et al [1][2][3][4][5][6][7] proposed a series of simple and efficient direct and indirect simulation techniques for accurate simulation of fluid-solid coexistence. These approaches are based on extensions or generalizations of the constrained cell model 8,9 description of the solid phase.…”
mentioning
confidence: 99%
See 1 more Smart Citation